Kajian Biodegradasi Filem Plastik Campuran Polimer Sintetik dengan Biopolimer dalam Larutan Air - Octaviani, Melzi; Dewi, Asiska Permata; Boestari, Agusri; Zaini, Erizal; Djamaan, Akmal (Fakultas Farmasi Universitas Andalas, 2012)
A study on degradation of plastic film of the mixture of polystyrene sintetic polymers (PS) with poli(3-hidroxyibutirat) [P(3HB)] dan poli(3-hidroksibutirat-ko-3-hidroxyvalerat) [P(3HB-ko-3HV)] biopolymers in-vitro and in-vivo has been done. The assay was done by immersion test method in aquadest, river water at various pH of 4,6,8, and 10 respectively. Degradation rate was determined by linear regression with parameters including : t 50%, t 95% and rate constant (k). Degradation rate of plastic film of 1 PS/P(3HB) 95:5 at pH 6 was the fastest with k = 0,79 % week, t 50 % = 63,06 week and t 95 % = 119,84 week, followed by PS/P(3HB) 90 : 10 with k = 1,22 % / week, t 50 % = 41,25 week and t 95 % = 78,21 week and PS/P(3HB) 80 : 20 with k = 3,16 % week, t 50 % = 15,81 week and t 95 % = 30,05 week while pure PS plastic film (100 : 0 ) did not degraded at all. The degradation rate of a mixture of plastic film in river water, PS/P(3HB-ko-3HV) 95:5 showed k= 0,64 % week, t 50 % = 82,63 week and t 95 % = 157,17 week, PS/P(3HB-ko-3HV) 90:10 with k = 0,69 % week, t 50 % = 72,16 week and t 95 % = 137,4 week ; PS/P(3HB-ko-3HV) 85:15 with k = 0,74 %/week, t 50% = 66,79 week and t 95% = 127,32 week, while the pure PS plastic film (100:0) did not degrade.